Decision Support System for Choosing the Best Doctor at Sari Mutiara Hospital Using the Fuzzy Tsukamoto Method - Leliana Harahap; Sartika Dewi Purba (Jurnal ICT : Information and Communication Technologies, 2021)
Doctors are medical personnel who are allowed to practice medical without having to have a specific specialty, and in the hospital there are several specialist doctors, one of which is an obstetrician who is an obstetrician and midwife who has an official title of Sp.OG. So far, the decision making on the selection of the best doctor carried out by the assessment team often faces problems in determining the best doctor candidate where the results obtained are ineffective in determining the best doctor which is decided by means of deliberation meetings. So of the many best doctor candidates who have met the criteria, not all will be the recipients of the best doctor candidates. This is because there is no objective method to make a quick choice based on the doctor's data which is correct according to the results of the deliberation meeting. By referring to the solution provided by Fuzzy Tsukamoto in helping to make a decision, an assessment team can quickly make a decision on the best doctor candidate as desired by comparing all the existing criteria. A decision support system is generally defined as a system that is capable of producing solutions and handling problems. Decision support systems are not intended to replace the role of decision makers, but rather to assist and support decision makers. This Fuzzy Tsukamoto method can determine the preference value of each alternative